INTERNATIONAL TRANSPORT LOGISTICS OF UKRAINE IN THE POSTWAR PERIOD - Куць, Надія (SWorldJournal, 2025)
The article discusses the main challenges and prospects for the development of international transport logistics in Ukraine in the context of post-war recovery. The efficient functioning of the logistics system ensures Ukraine's integration into global tr